Ecotourism development Ujung Kulon national park (tnuk) as a tourist destination - Suherman, . (Opción, 2019)
Estimation of the number of visits by socioeconomic factors to each individual newborn calves per year visits was made by using the Individual Travel Cost Method (ITCM) with use of descriptive and explanatory survey method. As a result, to balance the demand for visits to the national park and the protection of resources needs to put in place a strategy/ plan so that both of these can be carried out properly. In conclusion, cooperation and synergy between all stakeholders is the answer to overcome various obstacles in the development of ecotourism.